Living in the moment: Effects of time perspective and emotional valence of episodic thinking on delay discounting - Lin, Henry (2014)
Excessive delay discounting (DD) has been related to various maladaptive behaviors, and may stem from a myopic focus on immediate gratification. Neuroimaging studies have shown that episodic future thinking (EFT) – vivid mental simulation of future experiences – may reduce DD by promoting consideration of delayed outcomes. However, the EFT manipulations in these experiments may have induced positive affect, which could independently enhance executive functions that facilitate self-regulation. To clarify the mechanism of this effect, 87 participants were randomized to visualize neutral- or positive-valenced events expected to occur in the present or in the future while completing a standardized DD questionnaire. Working memory capacity, inhibitory control, the genotypes of 3 functional dopaminergic polymorphisms (DRD1 rs686, DRD2 rs1800497 and COMT rs4680), as well as an additive dopamine genetic risk score were assessed as potential moderators. The results indicate that EFT reduces DD primarily by shifting the time perspective of intertemporal decision-making, and that this effect is moderated by working memory capacity. In addition, positive episodic thinking may independently attenuate the protective effects of high working memory capacity, high inhibitory control, and lower dopamine genetic risk scores on DD. The current findings dovetail with previous research to suggest that the time perspective and emotional valence of episodic thinking may dynamically shape intertemporal choice, perhaps in part by transiently modulating executive function and dopaminergic neurotransmission.